Comparison of nicardipine versus labetalol for time to alteplase administration in acute ischemic stroke - Alex Huang; Dennis Parker; Dennis Parker; Rachel Wein (Frontiers in Neurology)
BackgroundThough the acute management of hypertension in patients with ischemic stroke has been associated with prolonged time to alteplase administration, it is unclear whether the choice of antihypertensive agent also influences this outcome. The purpose of this study was to evaluate the difference between nicardipine and labetalol on door-to-needle time in hypertensive patients with acute ischemic stroke.MethodsThis multicenter, retrospective study included all adult patients presenting to the emergency department (ED) with acute ischemic stroke between January 2018 and August 2023 who received at least one dose of labetalol or nicardipine prior to thrombolytic therapy. Patients with concomitant acute myocardial infarction, bradycardia, or history of severe aortic stenosis were excluded from the analysis. The primary outcome of this study was the time from ED arrival to alteplase administration.ResultsA total of 481 patients were included in the analysis: 400 (83%) received no antihypertensive, 68 (14%) received labetalol, and 13 (3%) received nicardipine prior to alteplase administration. We found no statistically significant difference in median door-to-needle times in patients who received labetalol vs. those that received nicardipine (63 min vs. 81 min, p = 0.19). Patients who did not require antihypertensive treatment had a shorter median door-to-needle time than those treated with either labetalol or nicardipine (58 min vs. 67 min, p = 0.02).ConclusionThis study did not demonstrate a significant difference in time to alteplase administration between patients treated with labetalol vs. nicardipine. Further studies are needed to determine whether the choice of antihypertensive agent used in acute ischemic stroke significantly affects clinical outcomes.